Embryological aspects in autoimmune pancreatitis, proposal of autoimmune dorsal pancreatitis. (July 2013) - Hara, Seiichi; Kamisawa, Terumi; Tabata, Taku; Kuruma, Sawako; Chiba, Kazuro; Kuwata, Go; Fujiwara, Takashi; Egashira, Hideto; Koizumi, Koichi; Fujiwara, Junko; Arakawa, Takeo; Momma, Kumiko; et al.
Abstract Objective. We examined the anatomy of the pancreatic duct system in patients with autoimmune pancreatitis (AIP) from the standpoint of embryological pancreatic primordial. Material and methods. The pancreatic duct system involved in 83 AIP patients was embryologically divided into both ventral and dorsal pancreatic ducts (VD type), only the dorsal pancreatic duct (D type), or only the ventral pancreatic duct (V type). Results. The 83 AIP patients were divided into 62 VD type, 20 D type, and 1 V type. Obstructive jaundice was significantly more frequent in VD type (87%) than in D type (0%; p < 0.01), and abdominal pain was more frequent in D type (24%) than in VD type (2%; p < 0.01). Stenosis of the lower bile duct was detected in 98% of VD type and 15% of D type (p < 0.01). In the 67 patients with involvement of the pancreatic head, only the dorsal pancreatic duct was involved with a normal ventral pancreatic duct in four patients (D type). In the four D-type patients, the pancreatic duct system showed complete pancreas divisum (n = 1), incomplete pancreas divisum (n = 2), or normal pancreatic duct system (n = 1). Stenosis of the lower bile duct was seen in three patients, but was mild, resulting in no obstructive jaundice. Three patients reported abdominal pain and one patient developed acute pancreatitis. Conclusions. We propose a new entity of "autoimmune dorsal pancreatitis" in which only the dorsal pancreas is involved, and involvement of the lower bile duct and obstructive jaundice is rare.